The Compartive Study of Prevalence of Ulcerative Colitis in General Population with MS Patients - Masood Etemadifar; Ahmad Chitsaz; Maryam Mollabashi; Azam Moradi; Mehdi Teimouri; Shirin Ashkbosi (مجله دانشکده پزشکی اصفهان, 2011)
Background: Multiple sclerosis and ulcerative colitis are two chronic and disabling disease that cause many problems to patients. Until now there is not a good study to determine relation and similarity between this disease. The aim of this study is to compare the prevalence of ulcerative colitis in general population with MS patients. Methods: In this cross-sectional study from March 2008 to September 2009, 250 patients with MS were compared with 250 persons of general population without MS, to evaluate the prevalence of ulcerative colitis. Finding: The mean of age was not different in two groups. 2% (5 persons) of patients with multiple sclerosis had ulcerative colitis, but general population had not ulcerative colitis. This difference was clearly, significant (P = 0.03). Conclusion: In this study as the other study reports, the prevalence of ulcerative colitis among patients with multiple sclerosis is more than normal population and it seems that some predisposing factors are responsible in two diseases. So more gastrointestinal evaluation should be done in MS patients with gastrointestinal sign and symptoms to rule out ulcerative colitis.